Familia disfuncional y su incidencia en el rendimiento escolar en un caso atendido en DECE - Chafla Pilatuña, Zoraida Marizol (2020)
The present case study aimed to explain the incidence of the dysfunctional family in the school performance of a 10-year-old child, it is understood by family dysfunctionality is when there are conflicts in the family which prevents developing in a functional way causing consequences in the development and school performance of the child. To obtain the diagnosis of family dysfunctionality, several resources were used such as: clinical history, psychometric test, semi-structured interview and clinical observation. It could be evidenced that the family system was being affected by the fights and separation by the parents being this a factor that caused the low academic performance. Therefore, a psychotherapeutic plan based on systemic therapy will be designed to address this problem.